Impact of tropical cyclones on a baroclinic jet in the ocean - Sutyrin, G.; Ginis, I. (Морской гидрофизический журнал, 2013)
The initial evolution of a baroclinic jet under influence of a barotropic flow induced by the tropical cyclones is considered using a two-layer model and the thin-jet approximation. In spite of antisymmetric structure of the barotropic flow, the jet meander growth due to the barotropic flow advection is shown to favor an anticyclonic meander to the right of the storm track. This enhancement of the anticyclonic meander is found to be related to the dispersion properties of frontal waves along the jet described by the thin-jet theory and coupling with deep eddies developing in the lower layer during the jet meandering. У рамках двошарової моделі та в наближенні тонкого струменя розглядається еволюція бароклинного струменя, викликаного баротропною течією, індукованою тропічним циклоном. Показано, що, не дивлячись на антисиметричну структуру баротропної течії, її адвекція призводить до меандрування бароклинного струменя та до зростання головним чином антициклонічного меандру праворуч від штормтрека. Знайдено, що посилення антициклонічного меандру пов'язане з дисперсійними властивостями фронтальних хвиль (які описуються у рамках теорії тонкого струменя) і з взаємодією з глибинними вихорами, які розвиваються в нижньому шарі океану при меандруванні бароклинного струменю. В рамках двухслойной модели и в приближении тонкой струи рассматривается эволюция бароклинной струи, вызванной баротропным течением, индуцированным тропическим циклоном. Показано, что, несмотря на антисимметричную структуру баротропного течения, его адвекция приводит к меандрированию бароклинной струи и к росту главным образом антициклонического меандра справа от штормтрека. Обнаружено, что усиление антициклонического меандра связано с дисперсионными свойствами фронтальных волн (описываемых в рамках теории тонкой струи) и с взаимодействием с глубинными вихрями, развивающимися в нижнем слое океана при меандрировании бароклинной струи.